Governance and Accountability Crisis of State-Owned Enterprise Issuers: A Case Study of PT Indofarma Tbk (INAF.IJ) Within the Framework of Capital Market Law and Anti-Corruption Enforcement - Bondan Christiandinata (International Journal Labs, 2026)
This paper analyzes the governance and accountability crisis of PT Indofarma Tbk (INAF), a State-Owned Enterprise (SOE) listed on the Indonesia Stock Exchange, in the perspective of capital market law, limited liability company law, and law on the eradication of corruption. This research departs from the deterioration of INAF's financial performance from 2020 to 2022, the change in auditor opinion to be reasonable with exceptions, the findings of the investigative audit of the Financial Audit Agency which indicate state losses, and the process of enforcing the criminal law of corruption against the Company's management. Using a normative juridical approach and case study, this paper examines the relationship between violations of information disclosure obligations, weak internal control, failure to supervise company organs, and criminal liability of SOEs Board of Directors. The results of the study show that the INAF case is not solely a business failure, but a manifestation of systemic violations of the principles of fiduciary duty, transparency, and accountability of public issuers. Furthermore, this study confirms a shift in the paradigm of Indonesian capital market law enforcement from an administrative compliance approach to an investigative audit-based law enforcement approach and economic criminal law. This paper concludes that public SOE governance reform requires stronger synergy between capital market regulators, law enforcement officials, and internal corporate oversight mechanisms to protect the interests of investors and maintain the integrity of Indonesia's capital market.